2005
DOI: 10.1159/000086428
|View full text |Cite
|
Sign up to set email alerts
|

<i>TAU</i> Haplotype and the <i>Saitohin</i> Q7R Gene Polymorphism Do Not Influence CSF Tau in Alzheimer’s Disease and Are Not Associated with Frontotemporal Dementia or Parkinson’s Disease

Abstract: Background: Recent studies have described Saitohin(STH), a gene located in the human TAU gene. The corresponding protein shows a similar tissue expression to tau, which is involved in many neurodegenerative disorders including Alzheimer’s disease (AD), frontotemporal dementia (FTD) and Parkinson’s disease (PD). A single nucleotide polymorphism in the STH gene has been suggested to be involved in sporadic AD and is in complete linkage disequilibrium with the TAU haplotype H1. Objective: A case-control study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 98 publications
4
16
0
Order By: Relevance
“…Association of the H1 haplotype at the MAPT locus with PSP and CBD has been described and replicated8; however, association studies of variants at MAPT in PD have produced conflicting results14,15. Our data provide unequivocal evidence for an association of the MAPT locus with PD.…”
supporting
confidence: 54%
“…Association of the H1 haplotype at the MAPT locus with PSP and CBD has been described and replicated8; however, association studies of variants at MAPT in PD have produced conflicting results14,15. Our data provide unequivocal evidence for an association of the MAPT locus with PD.…”
supporting
confidence: 54%
“…35 Another study found AD patients who are tau H1/H1 haplotype carriers have lower CSF tau levels as compared to H1/H2 carriers. 36 We did not observe either effect but differences in sample size, age, and gender distribution may have influenced our findings since the gender effect was not present in the AD2 group.…”
Section: Discussionmentioning
confidence: 55%
“…19 Two studies showed an over-representation of H1 haplotype in FTD, 7,8 whereas other studies fail to find any relation with the haplotypes and the risk for the disease. 56,57 Therefore, H1…”
Section: -52mentioning
confidence: 99%